Endoscopic endonasal skull base surgery in pediatric patients. A single center experience. Issue 12 (December 2018) - Giovannetti, Filippo; Mussa, Federico; Priore, Paolo; Scagnet, Mirko; Arcovio, Elena; Valentini, Valentino; Genitori, Lorenzo
Abstract: Object: At present, a minimally invasive endoscopic endonasal approach is considered an efficient option for lesions affecting the anterior and middle skull base with sellar and parasellar region involvement. In this study we will retrospectively analyze the pediatric patients that we have been treating in the same medical center for the past four years, using an endoscopic approach in the skull base. Methods: We performed a retrospective chart and imaging review of pediatric patients who underwent endoscopic endonasal skull base surgery (ESBS) at the Meyer Children's Hospital, (Azienda Ospedaliero Universitaria Meyer), in Florence, from January 2012 to July 2016. Results: Mean age was 12, 5 years; 28 (65%) of the 44 patients were females. Skull base lesions were broadly classified as either bony abnormalities (4 cases) or skull base tumors (40 cases). The postoperative clinical follow-up duration ranged from 2 to 36 months. The two more frequently occurring diseases in our study were: craniopharyngioma and pituitary adenoma. Conclusions: After reviewing the international literature about pediatric endoscopic endonasal approach to skull base, we can affirm that our study is the world's second broadest work for number of records. While compiling this report, we have examined the first 40 consecutive pediatric patients to undergo ESBS at our institute. The appearance of postoperative complications is consistent with other international studies, confirming ESBS being feasible and safe even in the pediatric population. Level of evidence: 4.